First report on the distribution of Aegiceras corniculatum (L.) Blanco (Primulaceae) from the Nicobar archipelago, India - Vedagiri Thirumurugan; Anoop Raj Singh; G. Gnanasekaran; Nehru Prabakaran (Ocean and Coastal Research)
The 2004 Sumatra-Andaman earthquake (9.3 Mw) and subsequent tsunami caused upliftment and subsidence throughout the Andaman and Nicobar archipelago. This incident has significantly impacted the mangroves (97% vegetation loss) and coastal ecosystems of the Nicobar archipelago. Interestingly, the coastal subsidence has also created new intertidal habitats in the erstwhile agricultural lands and terrestrial forests, which provided an opportunity for the colonization of mangrove species. During our long-term monitoring of mangrove colonization in the Nicobar archipelago, we collected Aegiceras corniculatum  (L.) Blanco (Primulaceae) from Alreak, in Nicobar Islands. The occurrence of this species forms a new distributional record for the Nicobar archipelago. The present article provides detailed information on its taxonomy, ecology, and discusses the potential future spread of this species in the Nicobar Islands.